Parent-child relationship and depression among adolescents in Selangor, Malaysia - Ang, Chun Ee; Arshat, Zarinah (Invention Journals, 2017)
Depression is one of the internalizing problems that often goes unnoticed. It is commonly known as simply sadness and disappointment to life events encountered. Present research study aimed to investigate the relationship between parent-child relationship and adolescent depression. Results revealed that gender had positive significant relationship with adolescent depression. Family monthly income, father-child relationship and mother-child relationship were found to have negative significant relationship with adolescent depression.